The Role of FLIR ONE Thermography in Complex Regional Pain Syndrome: A Case Series. (April 2021) - Dhatt, Saroop; Krauss, Emily M.; Winston, Paul
Abstract : Abstract: Complex regional pain syndrome remains a debated syndrome characterized by symptoms and signs, including pain, sensory disturbances, thermal asymmetry, edema, and motor impairments. Thermography is a tool that assesses skin surface temperature distribution. Current literature focuses on the role of thermography for diagnostic purposes; however, its role in monitoring the response to treatment in complex regional pain syndrome is unclear. We present a case series of four patients with complex regional pain syndrome where a FLIR ONE thermal imaging camera (FLIR Systems, Inc, Wilsonville, OR) was used to assist in the diagnosis of complex regional pain syndrome, capture the effects of diagnostic nerve blocks to evaluate a peripheral nerve contribution to complex regional pain syndrome, as well as monitor and assess treatment efficacy with prednisone and surgery. Four patients were screened by clinical assessment to meet the Budapest Criteria. The thermal images revealed improvement in the temperature distribution after therapeutic intervention. We also noted temporary but immediate changes on thermal imaging with diagnostic nerve blocks. Our cases suggest that the FLIR ONE thermal imaging camera has the potential to be an accessible monitoring tool to assist in diagnosis and assess treatment efficacy in complex regional pain syndrome over time. Abstract : Supplemental digital content is available in the text.